Research in Journal Of Organization Design, 2012-2018 - Charles C. Snow (Journal of Organization Design, 2018)
Articles published in the Journal of Organization Design (JOD) from its inception in 2012 until mid-2018 are reviewed and summarized according to their type: research, point of view, translational, case study, research primer, and Organization Zoo. Using multiple assessment criteria, JOD's contributions to the field of organization design are identified. Important topics for future research on organization design are suggested.
Keywords: 650; Organization design; Organization design practice; Organization design theory and research